2008
DOI: 10.1021/jp710704v
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Polyethersulfone/Sulfonated Polyimide Blend Membrane for Proton Exchange Membrane Fuel Cell

Abstract: Solution-cast membranes from sulfonated polyimide (SPI) and its blend were prepared from polyethersulfone (PES) and SPI. The water uptake and swelling were tested and compared between the SPI membrane and the four kinds of blend membranes. Through comparison of the stability of the membranes, we concluded that the PES could greatly increase the stability of the whole membrane and restrict the swelling. However, the PES did not decrease the water uptake very much. We also compared the fuel cell performance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…A variety of different blended polymer pairs chosen to introduce specific interactions have been considered as PEM candidates for fuel cells application [113][114][115][116][117]. Such interactions are reported to improve compatibility in 'two blend' polymers and also reduce methanol cross over in DMFCs.…”
Section: Blend Polyelectrolyte Complex Membranesmentioning
confidence: 99%
“…A variety of different blended polymer pairs chosen to introduce specific interactions have been considered as PEM candidates for fuel cells application [113][114][115][116][117]. Such interactions are reported to improve compatibility in 'two blend' polymers and also reduce methanol cross over in DMFCs.…”
Section: Blend Polyelectrolyte Complex Membranesmentioning
confidence: 99%
“…Despite these potential advantages, however, their application in fuel cell membranes is hampered by their instability toward hydrolysis and heat. Introducing flexible linkages, separating the sulfonic acid group from the diamine parts, and using aliphatic diamines could improve the stability of these materials, but research on more stable membranes would remain highly desirable [34].…”
Section: Introductionmentioning
confidence: 99%
“…Kallitsis et al 29 investigated polybenzimidazole/sulfonated polysulfone blend membranes, and the miscible structure was proven. Yi et al 30 reported a blend membrane prepared from nonsulfonated polyether DOI 10.1007/s13233-012-0018-1 *Corresponding Author. E-mail: ythong@krict.re.kr sulfone and SPI, and the stability of the SPI was greatly improved.…”
Section: Introductionmentioning
confidence: 99%